Microfabrication and surface functionalization of soda lime glass through direct laser interference patterning - Soldera, Marcos Maximiliano (2021)
All-purpose glasses are common in many established and emerging industries, such as microelectronics, photovoltaics, optical components, and biomedical devices due to their outstanding combination of mechanical, optical, thermal, and chemical properties. Surface functionalization through nano/micropatterning can further enhance glasses’ surface properties, expanding their applicability into new fields. Although laser structuring methods have been successfully employed on many absorbing materials, the processability of transparent materials with visible laser radiation has not been intensively studied, especially for producing structures smaller than 10 µm. Here, interference-based optical setups are used to directly pattern soda lime substrates through non-lineal absorption with ps-pulsed laser radiation in the visible spectrum. Line-and dot-like patterns are fabricated with spatial periods between 2.3 and 9.0 µm and aspect ratios up to 0.29. Furthermore, laserinduced periodic surface structures (LIPSS) with a feature size of approximately 300 nm are visible within these microstructures. The textured surfaces show significantly modified properties. Namely, the treated surfaces have an increased hydrophilic behavior, even reaching a super-hydrophilic state for some cases. In addition, the micropatterns act as relief diffraction gratings, which split incident light into diffraction modes. The process parameters were optimized to produce high-quality textures with super-hydrophilic properties and diffraction efficiencies above 30%.